Newly emerging diseases of marine turtles, especially sea turtle egg fusariosis (SEFT), caused by species in the Fusarium solani complex (FSSC) - Frank H. Gleason; Monika Allerstorfer; Osu Lilje (Mycology, 2020)
Sea turtles are presently considered severely endangered species that are historically threatened by many environmental factors. Recently, additional threats to sea turtles from two pathogenic species of fungi in the Fusarium solani species complex (F. falciforme and F. keratoplasticum) have been identified. These species infect marine turtle eggs, causing sea turtle egg fusariosis, and kill their embryos, with recent reports of hatch-failure in seven globally distributed species of endangered sea turtles (Caretta caretta, Chelonia mydas, Dermochelys coriaceae, Eretmochelys imbricata, Lepidochelys olivacea, Lepidochelys kempi and Natator depressus). Mycelia and spores of pathogenic species of Fusarium are produced in disturbed terrestrial soils and are transported to the ocean in coastal run off. We propose that these fungi grow on floating particles of plant tissues (leaves and wood), animal tissues, silt and plastics, which are carried by wind and currents and the turtles themselves to the beaches where the turtles lay their eggs.